Failure Mode and Effects Analysis (FMEA) for a Maintenance System Development: A Case Study of Meat Processing - ปัญญางาม, วราธร (Engineering and Technology Horizons, 2020)
This paper proposed the concept of the Failure mode and effects analysis (FMEA) in the context of risk management to develop maintenance system. There are fourteen different machine of meat processing which are focused. The definition and level of Severity (S) Occurrence (O) and Detect (D) are revised to link with the Six major losses and the real operation management of a case study. After implement new maintenance system, there are not only number of high risk causes of machine losses which was treat to be zero, but also number of medium risk can be decreased.